2000
DOI: 10.1007/s003390051073
|View full text |Cite
|
Sign up to set email alerts
|

Laser microstructuring of steel surfaces for tribological applications

Abstract: Laser technique is employed to improve substantially the tribological behavior of microstructured stainless steel surfaces. The laser-generated patterns consisting of precisely ablated microcraters were produced using a flash lamp pumped, Q-switched Nd:YAG laser. The rims of resolidified melt around the craters are typical features of laser-produced microstructures and the laser parameters were established where their extent was notably reduced. The remaining rims could easily be removed by gentle polishing. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(59 citation statements)
references
References 5 publications
0
55
0
1
Order By: Relevance
“…This approach can be applied to a wide range of materials including metals [16], polymers [17], ceramics [18]. However, due to the limitations related to production times and manufacturing costs, other innovative production methods are being explored -these, along with their advantages over LST, have recently been reviewed by Costa and Hutchings [19].…”
Section: Surface Texturementioning
confidence: 99%
“…This approach can be applied to a wide range of materials including metals [16], polymers [17], ceramics [18]. However, due to the limitations related to production times and manufacturing costs, other innovative production methods are being explored -these, along with their advantages over LST, have recently been reviewed by Costa and Hutchings [19].…”
Section: Surface Texturementioning
confidence: 99%
“…9,10 In the case of cross-hatch honing, the effect of the honing angle relative to the direction of sliding has been investigated through numerical analysis by Michail and Barber 11 and Spencer et al 12 In recent years, a host of other surface treatment techniques have emerged, including laser surface texturing (see, for example, the papers by Ryk et al, 13 Kovalchenko et al, 14 Rahnejat et al 15 and Etsion and Sher 16 ), lithographic techniques and various mechanical techniques such as engraving, indentation, embossing and vibro-rolling. Dumitru et al 17 and Andersson et al 18 have provided comprehensive reviews of the various techniques. Kovalchenko et al 14 reported a series of lubricated sliding experiments with different surfaces, consisting of rough ground, very smooth and dimpled surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to boundary and mixed lubrication, patterned surfaces can store oil in order to act as a secondary oil source or trap wear particles to reduce abrasive wear. This can lead to an increase in the oil film lifetime or to an improved wear behavior [39][40][41][42]. Regarding dry friction, surface patterns typically reduce the contact area and store wear particles, thus lowering the resulting coefficient of friction (COF) and avoiding stiction, as well as improving adhesion [21,43].…”
Section: Surface Patterns For An Improved Tribological Performancementioning
confidence: 99%